The Effect of Spirulina Platensis in Feed for Color Brightness, Growth, Feed Efficiency and Survival Rate of Rainbow Boesemani Fish (Melanotaenia boesemani) - Muhammad Reyza Dwi Satria; Diana Chilmawati; Sri Hastuti; Subandiyono Subandiyono (Sains Akuakultur Tropis : Indonesian Journal of Tropical Aquaculture, 2022)
Boesemani rainbow is one of ornamental fish that have good demand on ornamental fish lover either in domestic market or foreign market because having beautiful color and unique body shape. The color brightness of rainbow boesemani (Melanotaenia boesemani) can be enhanced by coloration. One of them by using Spirulina platensis flour as coloration. The purpose of this study was to examine the effect S. platensis in fish feed and the dosage S. platensis to enhance color brightness, growth, feed efficiency and survival rate of rainbow boesemani. The research was conducted in January - Maret 2021 on Patriot Aquafarm, Semarang, Middle Java.  The test animals used were rainbow boesemani with length 2,5 ± 0,5 cm and a density of 10 fish / 6 liter. This study used an experimental method with a completely randomized design (CRD) with 4 treatments and 3 replications of S. platensis flour with different dosage in 100g feed. The different treatments are A. 0%,  B. 0,5%, C. 1%, and D. 1,5%. The results obtained from the study showed that the highest hue value in treatment C (1%) with an increase 41.67± 7.57, the highest absolute weight value in treatment B (0,5%) with an increase 3,51 ± 0,19, feed comsumtion total 4.81 ± 0,28, feed convertion ratio 1,59±0,06 and survival rate 100.00 ± 00.00%. The results of water quality observations were in the form of DO ranging from 7,2 - 9,5 mg / l, pH 7,9 - 9,0 and temperatures ranging from 24-30℃. The conclusion was that the increase S. platensis in feed had a significant effect on the color brightness, growth and feed convertion ratio. By increasing S. platensis with 1% dosage will resulting the highest brightness value and 0,5% dosage will resulting the highest growth value and feed convertion ratio.Keywords: Spirulina platensis, Melanotaenia boesemani, Coloration